2023
DOI: 10.3390/ijms241612718
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Molecular Events Underlying the Establishment of Axillary Meristem Region in Pepper

Abstract: Plant architecture is a major motif of plant diversity, and shoot branching patterns primarily determine the aerial architecture of plants. In this study, we identified an inbred pepper line with fewer lateral branches, 20C1734, which was free of lateral branches at the middle and upper nodes of the main stem with smooth and flat leaf axils. Successive leaf axil sections confirmed that in normal pepper plants, for either node n, Pn (Primordium n) < 1 cm and Pn+1 < 1 cm were the critical periods between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Various hormones, such as auxin/IAA, cytokinin (CTK), gibberellin (GA), and abscisic acid (ABA), are involved in the process of lateral bud germination [1,5]. For example, ABA can affect the expression of key transcription factors that maintain bud dormancy [6,7], while IAA [8][9][10], CTK [11,12], and GA [13] cooperatively promote germination and development of lateral buds in multiple plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various hormones, such as auxin/IAA, cytokinin (CTK), gibberellin (GA), and abscisic acid (ABA), are involved in the process of lateral bud germination [1,5]. For example, ABA can affect the expression of key transcription factors that maintain bud dormancy [6,7], while IAA [8][9][10], CTK [11,12], and GA [13] cooperatively promote germination and development of lateral buds in multiple plants.…”
Section: Introductionmentioning
confidence: 99%
“…Both types start shooting soon after the beginning of the rainy season [15,16]. Therefore, empirically, the rhizome buds germination of woody bamboos with a single shooting peak is generally considered to be induced by the regulation of endogenous hormone synthesis and transport following an increase in soil temperature and precipitation in the rainy season [8]. The previous studies indicated the mass fractions of various phytohormones fluctuated regularly during the shooting period, implying that antagonism or coordination of endogenous hormones, such as IAA, GA, and ABA, were key signaling factors for bamboo shoot initiation [17][18][19].…”
Section: Introductionmentioning
confidence: 99%